2023
DOI: 10.1038/s41598-023-31488-w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid oxidative fragmentation of polypropylene with pH control in seawater for preparation of realistic reference microplastics

Abstract: Various tiny plastic particles were retrieved from the sea and studied using scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDX) analysis to prepare realistic reference microplastics (MP). Most of the MP exhibited a diameter of < 20 × 10−6 m and 0.1–0.2 molar ratios of oxygen to carbon atoms (O/C), indicating that they primarily comprised polyethylene (PE), polypropylene (PP), and polystyrene (PS). It took a long time to reproduce such O/C ratios in standard laboratory weathering met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…This color change is due to the valence change of copper ions. We have previously reported that seawater drastically improved PP degradation performance during the AOP under pH control [15,25]. Cl − reacts with OH• generated by degradation actions such as solar irradiation and AOP in seawater and yields Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This color change is due to the valence change of copper ions. We have previously reported that seawater drastically improved PP degradation performance during the AOP under pH control [15,25]. Cl − reacts with OH• generated by degradation actions such as solar irradiation and AOP in seawater and yields Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Because the pH of seawater is around 8, the equilibrium is biased toward the less reactive ClO − , suppressing PP degradation in seawater [27]. We, therefore, adjusted the pH to shift the equilibrium toward ClOH [15] in Eq. (1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations